Association between tuberculosis and pregnancy outcomes: a retrospective cohort study of women in Cape Town, South Africa - Meehan, Sue-Ann; Hesseling, Anneke C.; Delft, Arne von; Marx, Florian; Hughes, Jennifer A.; Bock, Peter; Banke-Thomas, Aduragbemi; Dunbar, Rory; Phelanyane, Florence; Smith, Mariette; Osman, Muhammad (BMJ open, 2024)
Background Tuberculosis (TB) remains a leading cause of mortality among women of childbearing age and a significant contributor to maternal mortality. Pregnant women with TB are at high risk of adverse pregnancy outcomes. This study aimed to determine risk factors for an adverse pregnancy outcome among pregnant women diagnosed with TB. - Methods Using TB programmatic data, this retrospective cohort analysis included all women who were routinely diagnosed with TB in the public sector between October 2018 and March 2020 in two health subdistricts of Cape Town, and who were documented to be pregnant during their TB episode. Adverse pregnancy outcome was defined as either a live birth of an infant weighing <2500 g and/or with a gestation period <37 weeks or as stillbirth, miscarriage, termination of pregnancy, maternal or early neonatal death. Demographics, TB and pregnancy characteristics were described by HIV status. Logistic regression was used to determine risk factors for adverse pregnancy outcome. - Results Of 248 pregnant women, half (52%) were living with HIV; all were on antiretroviral therapy at the time of their TB diagnosis. Pregnancy outcomes were documented in 215 (87%) women, of whom 74 (34%) had an adverse pregnancy outcome. Being older (35-44 years vs 25-34 years (adjusted OR (aOR): 3.99; 95% CI: 1.37 to 11.57), living with HIV (aOR: 2.72; 95% CI: 0.99 to 4.63), having an unfavourable TB outcome (aOR: 2.29; 95% CI: 1.03 to 5.08) and having presented to antenatal services ≤1 month prior to delivery (aOR: 10.57; 95% CI: 4.01 to 27.89) were associated with higher odds of an adverse pregnancy outcome. - Conclusions Pregnancy outcomes among women with TB were poor, irrespective of HIV status. Pregnant women with TB are a complex population who need additional support prior to, during and after TB treatment to improve TB treatment and pregnancy outcomes. Pregnancy status should be considered for inclusion in TB registries.